2020
DOI: 10.31557/apjcp.2020.21.9.2531
|View full text |Cite
|
Sign up to set email alerts
|

Cornus Mas L improves Antioxidant Status in the Liver, Lung, Kidney, Testis and Brain of Ehrlich Ascites Tumor Bearing Mice

Abstract: C. mas L, is a medicinal plant that has a high level of antioxidant activity. C. mas L. is a plant that has high nutritional value and also has therapeutic properties. It grows in Asia and Europe. Especially in Turkey, it is grown in gardens for its fruit and it grows wild in northern Anatolian forests. (Kayaalp., 1996). There are numerous articles in the literature that demonstrate the antineoplastic mechanism of curcumin. C. Mas L is known to increase the rate of death of some types of cancer cells and stop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…prepared in various forms are promising in terms of antimicrobial, anti-inflammatory, antitumor, and antidiabetic activities (Alavian et al, 2014;Tiptiri-Kourpeti et al, 2019). It has also been reported that C. mas L increases the death rate of some cancer cells and stops the division of tumor cells (Yılmaz et al, 2020).…”
mentioning
confidence: 99%
“…prepared in various forms are promising in terms of antimicrobial, anti-inflammatory, antitumor, and antidiabetic activities (Alavian et al, 2014;Tiptiri-Kourpeti et al, 2019). It has also been reported that C. mas L increases the death rate of some cancer cells and stops the division of tumor cells (Yılmaz et al, 2020).…”
mentioning
confidence: 99%
“…Naturally, occurring antioxidant supplementation can be effectively restored redox homeostasis by neutralizing and removing excess oxidants. 30 So, administration of ASLE or ASLELN reversed the effect of EAC cells, by increasing SOD activity, and GSH content, and attenuating the EAC—mediated increase of MDA levels, demonstrating the ability of the extracts in reducing oxidative stress in tumor-bearing mice by modulating antioxidant levels. The reduction of oxidative stress in treated EST-bearing mice may be due to the antioxidant compounds content of these extracts as polyphenolic compounds and flavonoids as quercetin, that increase and have the free radical scavenging property, 31 confirming the antioxidant activity of the examined extracts especially ASLELN in the group (4).…”
Section: Discussionmentioning
confidence: 88%
“…Naturally, occurring antioxidant supplementation can be effectively restored redox homeostasis by neutralizing and removing excess oxidants . So, administration of ASLE or ASLELN reversed the effect of EAC cells, by increasing SOD activity, and GSH content, and attenuating the EACmediated increase of MDA levels, demonstrating the ability of the extracts in reducing oxidative stress in tumor-bearing mice by modulating antioxidant levels.…”
Section: Discussionmentioning
confidence: 93%
“…The oxidation of proteins is characterized by covalent modification in proteins, induced by different processes directly associated with progressive losses of the biochemical functions of a given protein 8 . Together, lipid peroxidation and protein oxidation cause disturbances in cellular functions that are associated with the initiation and promotion of carcinogenesis 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Increased lipid peroxidation and changes in antioxidant activity of catalase, superoxide dismutase, and glutathione are usually detected in cancer patients 10 . Thus, the Ehrlich experimental model has been widely used to study the biological processes associated with tumorigenesis 11 .…”
Section: Introductionmentioning
confidence: 99%